Manufacturing method of core assembly
The magnetic core addresses the challenges of heat treatment and brittleness in nanocrystalline thin strips by using a core assembly of block thin strips with laminated nanocrystalline thin strips, achieving improved magnetic properties and handling characteristics.
Patent Information
- Application Number
- JP2022547560
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-09
- Filing Date
- 2021-09-03
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2041-09-03
AI Technical Summary
Heat treatment of amorphous alloy thin strips for magnetic cores can lead to deteriorated magnetic properties and thermal runaway, requiring individual heat treatment conditions for each laminate configuration, and resulting in brittle nanocrystalline thin strips that are difficult to handle and prone to breakage.
A magnetic core with a core assembly of block thin strips, where nanocrystalline thin strips with a bcc-Fe phase are laminated, with lower iron loss in the central thin band compared to the surface thin bands, allowing for improved heat control and reduced brittleness.
The magnetic core achieves excellent magnetic properties with reduced iron loss and improved handling characteristics, while the core assembly's structure minimizes eddy current losses and enhances the stability and productivity of magnetic core production.
Smart Images

Figure 0007654320000009 
Figure 0007654320000010 
Figure 0007654320000011
Abstract
Description
[Technical field]
[0001] The present invention relates to a magnetic core and a magnetic component including such a magnetic core. [Background technology]
[0002] Patent Document 1 discloses a heat treatment device for a laminate of amorphous alloy ribbons, the heat treatment device including a lamination jig for holding the laminate of amorphous alloy ribbons, two heating plates for sandwiching the laminate from above and below in the lamination direction without contacting the lamination jig, and a heat control device for controlling the heating temperature of the two heating plates. By heat treating the laminate of amorphous alloy ribbons using this heat treatment device, a magnetic core including a laminate of ribbons of an Fe-based nanocrystalline alloy can be obtained.
[0003] Patent Document 2 discloses a laminated core for a motor having magnetic poles with a concave-convex surface formed by stacking a plurality of magnetic plates and alternating ridges and grooves along the direction of rotation of the motor, characterized in that welding parts for fixing the magnetic plates to each other are provided on the surfaces of the grooves formed in the magnetic poles. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP2017-141508A [Patent Document 2] International Publication No. 1999 / 21264 DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]
[0005] When the laminate of the amorphous alloy ribbon as described in Patent Document 1 is heat-treated, heat is generated during the crystallization of the amorphous alloy ribbon. If this heat is not appropriately controlled, the magnetic properties of the laminate of the obtained nanocrystalline alloy ribbon (nanocrystalline ribbon) may deteriorate, or thermal runaway may occur, causing the ribbon to burn. The number of layers of the laminate of the amorphous alloy ribbon is related to the heat generated in the laminate during heat treatment, and is also deeply related to the magnetic properties of the magnetic core including the laminate. For this reason, when preparing laminates with different numbers of layers to obtain multiple types of magnetic cores with different magnetic properties, it is necessary to set the heat treatment conditions individually for each laminate. If the amorphous alloy ribbon is heat-treated sheet by sheet without heat treatment as a laminate, the nanocrystalline ribbon obtained by the heat treatment is brittle and therefore difficult to handle, and is prone to damage such as cracks and chips in the process of stacking the nanocrystalline ribbon, which is problematic in terms of ensuring the quality of the magnetic core.
[0006] The present invention aims to provide a magnetic core having a structure in which nanocrystalline ribbons are laminated, and which has excellent magnetic properties. It is also an object of the present invention to provide a magnetic component including such a magnetic core. [Means for solving the problem]
[0007] In one aspect, the present invention for solving the above problems provides a magnetic core including a core assembly in which a plurality of block ribbons are arranged, the block ribbon having a structure in which a plurality of nanocrystalline ribbons having a bcc-Fe phase as a main phase are laminated, and the iron loss of the nanocrystalline ribbon located at the center in the thickness direction of the block ribbon is lower than the iron loss of the nanocrystalline ribbon located at the surface layer of the block ribbon. In the magnetic core, the fact that the iron loss of the nanocrystalline ribbon located at the center (center ribbon) is lower than the iron loss of the nanocrystalline ribbon located at the surface layer (surface ribbon) indicates that heat generation accompanying crystallization at both ends promotes crystallization in the center ribbon, and therefore the block ribbon including such a center ribbon becomes a member with low iron loss overall.
[0008] The nanocrystalline ribbon may be a heat-treated amorphous ribbon made of an amorphous alloy material. In this case, the thickness of the block ribbon is preferably such that the amorphous ribbon can generate the nanocrystalline ribbon by the heat treatment. If the thickness of the block ribbon is excessively large, there is a concern that the temperature cannot be controlled during the heat treatment of the amorphous ribbon, and the block ribbon may be burned. Specifically, the thickness of the block ribbon may be preferably 3 mm or less from the viewpoint of ease of control of the heat treatment of the amorphous ribbon.
[0009] The block ribbon may have a fixing portion where the nanocrystalline ribbons adjacent in the stacking direction are fixed to each other. Since it is possible to prepare a block ribbon in which a plurality of nanocrystalline ribbons are stacked and to manufacture a core assembly by arranging a plurality of the block ribbons, defects such as breakage of the nanocrystalline ribbon are less likely to occur compared to a case in which nanocrystalline ribbons are stacked one by one to form a laminated core, and as a result, it is possible to improve the quality of the magnetic core equipped with the core assembly.
[0010] In this way, since the core assembly is an assembly of a plurality of block ribbons, even if the fastening portion of the block ribbons is formed by welding or the like and has conductivity, the short-circuit path of the magnetic core including the core assembly is divided by the block ribbons. When a plurality of ribbons are integrated by welding or the like as described in Patent Document 2, the obtained magnetic core is also electrically integrated, so the short-circuit path of the magnetic core becomes longer. The longer the short-circuit path, the greater the eddy current loss of the magnetic core. Therefore, the magnetic core according to the present invention, which is divided into short-circuit path block ribbon units, is less likely to have increased iron loss, especially eddy current loss.
[0011] The relationship between the arrangement direction of the plurality of block ribbons constituting the core assembly and the stacking direction of the nanocrystalline ribbons in the block ribbon is arbitrary. The arrangement direction and the stacking direction may or may not be aligned with each other.
[0012] In the magnetic core having the above-mentioned fastening portion, the nanocrystalline ribbon may be welded to the fastening portion, and the fastening portion may be formed of a laser welded portion.
[0013] The magnetic core may have a shifted block ribbon group including a plurality of the block ribbons aligned along a first direction, the plurality of the block ribbons having portions where the fastening portions are not aligned in the first direction. A specific example of the first direction is the thickness direction of the nanocrystalline ribbon. The fastening portions may have different magnetic properties compared to other portions. Even in such a case, the magnetic core including the core assembly may have higher uniformity in magnetic properties by arranging the block ribbons so that the fastening portions included in the core assembly are not aligned in one direction.
[0014] In the magnetic core, the core assembly may be impregnated coated, which makes it difficult for the ribbon to peel off from the core assembly.
[0015] In another aspect, the present invention provides a magnetic component including the magnetic core described above. Effect of the Invention
[0016] According to the present invention, there is provided a magnetic core having a structure in which nanocrystalline ribbons are laminated and having excellent magnetic properties. The present invention also provides a magnetic component including the magnetic core. [Brief description of the drawings]
[0017] [Figure 1] FIG. 1(a) is a plan view showing a magnetic core according to an embodiment of the present invention, and FIG. 1(b) is a diagram showing a core assembly provided in FIG. [Diagram 2] FIG. 2A is a diagram showing a block ribbon included in the core assembly shown in FIG. 1B, and FIG. 2B is a plan view of the block ribbon. [Diagram 3]FIG. 1A is an example of a fastening portion provided on a block ribbon, showing the case where cutting and welding of the ribbon laminate are performed simultaneously (melting), and FIG. 1B is another example of a fastening portion provided on a block ribbon, showing the case where a portion of the cut surface of the ribbon laminate is welded. [Figure 4] (a) A diagram showing one modified example of a core assembly provided in a magnetic core according to one embodiment of the present invention, (b) a diagram showing another modified example of a core assembly provided in a magnetic core according to one embodiment of the present invention, and (c) a diagram showing another modified example of a core assembly provided in a magnetic core according to one embodiment of the present invention. [Diagram 5] 4 is a flowchart showing an example of a method for manufacturing a magnetic core according to an embodiment of the present invention. [Figure 6] 6 is a flowchart showing another example of the method for manufacturing a magnetic core according to an embodiment of the present invention. [Figure 7] 6 is a flowchart showing another example of the method for manufacturing a magnetic core according to the embodiment of the present invention. [Figure 8] 8(a) is an explanatory diagram of a manufacturing process of a hoop material made of an amorphous ribbon for forming a nanocrystalline ribbon provided in a magnetic core according to one embodiment of the present invention, (b) is an explanatory diagram of the configuration of a hoop material made of an amorphous ribbon manufactured by the manufacturing process of FIG. 8(a), and (c) is a diagram illustrating the punched portion of the hoop material made of an amorphous ribbon shown in FIG. 8(b). [Figure 9] 9(a) is a diagram showing a composite laminate obtained by dividing a hoop material made of an amorphous ribbon shown in FIG. 8(b), (b) is a diagram explaining the heat treatment of the composite laminate in FIG. 9(a), and (c) is a diagram showing the arrangement of a heat sink (heater) in the heat treatment in FIG. 9(b). [Figure 10] 10(a) is a diagram for explaining a modified example of the heat treatment of the coupled laminate of FIG. 9(b), and FIG. 10(b) is a plan view showing the shape of a heat sink used in the heat treatment of FIG. 10(a). [Figure 11] 10(a) is a plan view showing an example of a block ribbon produced by the production method shown in the flowchart of FIG. 7, and (b) is a diagram illustrating a fastening portion of the block ribbon of FIG. 10(a). [Figure 12] 12(a) is a plan view showing the shape of an amorphous ribbon for forming a core assembly included in a magnetic core according to another embodiment of the present invention, and FIG. 12(b) is a diagram showing the shape of a block ribbon formed from the amorphous ribbon of FIG. 12(a). [Figure 13] 13(a) is a diagram showing a core assembly including the block ribbon of FIG. 12(b), and FIG. 13(b) is a diagram showing a core assembly obtained by further combining the core assemblies of FIG. 13(a). [Figure 14] 14(a) is an external view of a motor, which is an example of a magnetic product using a magnetic component having a magnetic core according to one embodiment of the present invention, (b) is an external view of a rotor, which is one of the magnetic components included in the motor of FIG. 14(a), and (c) is an external view of a stator, which is another of the magnetic components included in the motor of FIG. 14(a). [Figure 15] FIG. 2 is an explanatory diagram of a heat treatment processing device used in the heat treatment step of the examples. [Figure 16] 1 is a graph showing the results of Example 1. [Figure 17] 1 is a graph showing the results of Example 2. [Figure 18] 1 is a graph showing the results of Example 3. [Figure 19] 1 is a graph showing the results of Example 4. [Figure 20] 1 is a graph showing the results of Example 5. [Figure 21] 1 is a graph showing the results of Comparative Example 1. [Figure 22] 1 is a graph showing the dependence of core loss and crystal grain size on the number of sheets based on the results of an example. [Figure 23] 1 is a graph showing the dependency of iron loss and crystal grain size on lamination thickness based on the results of an example. [Figure 24] 1 is a graph showing the relationship between the number of layers and the heat treatment temperature based on the results of an example. [Diagram 25] 1 is a graph showing the relationship between the laminate thickness and the heat treatment temperature based on the results of an example. BEST MODE FOR CARRYING OUT THEINVENTION
[0018] Hereinafter, an embodiment of the present invention will be described with reference to the drawings. In the following description, the same members are denoted by the same reference numerals, and the description of members that have already been described will be omitted as appropriate.
[0019] Fig. 1(a) is a plan view showing a magnetic core according to one embodiment (first embodiment) of the present invention. Fig. 1(b) is a view showing a core assembly provided in Fig. 1(a). Fig. 2(a) is a view showing a block ribbon provided in the core assembly shown in Fig. 1(b). Fig. 2(b) is a plan view of the block ribbon.
[0020] The magnetic core 100 according to the first embodiment has the shape of a motor stator, as shown in Fig. 1(a). Specifically, the magnetic core 100 has a cylindrical main body 10 having a through hole 20 passing through a central axis along the Z1-Z2 direction, and a plurality of teeth 30 extending radially (in the XY plane) from the outer surface of the cylindrical main body 10. The magnetic core 100 shown in Fig. 1 has 12 teeth 30, and a tip portion 40 having a protrusion protruding in the circumferential direction is located at the outer end of each tooth 30.
[0021] The magnetic core 100 is formed by applying an impregnation coating to the core assembly 50 made of a soft magnetic material shown in FIG. 1(b). The impregnation coating is formed by attaching a coating material made of a resin-based material to the surface of the core assembly 50 and impregnating it. The coating material is made of, for example, epoxy resin. The thickness of the impregnation coating is set so that the core assembly 50, which is a conductor, is appropriately covered and the magnetic core 100 has appropriate insulation properties. As a non-limiting example, the thickness of the impregnation coating is 0.1 μm to 5 μm.
[0022] The core assembly 50 is composed of a plurality of block ribbons 51. The core assembly 50 shown in Fig. 1(b) is composed of five block ribbons 51, 52, 53, 54, and 55 stacked in the Z1-Z2 direction.
[0023] The block ribbon 51 is a laminate of a plurality of nanocrystalline ribbons 511. The nanocrystalline ribbons 511 are made of a nanocrystalline alloy material having a bcc-Fe phase as a main phase. The block ribbon 51 shown in FIG. 2(a) includes a laminate of n nanocrystalline ribbons 511 in the Z1-Z2 direction. The iron loss of the nanocrystalline ribbon (central ribbon) located at the center of the thickness direction (Z1-Z2 direction) of the block ribbon 51 is lower than the iron loss of the nanocrystalline ribbon (surface layer ribbon) located at the surface layer of the block ribbon 51. The fact that the iron loss of the central ribbon is lower than the iron loss of the surface layer ribbon indicates that heat generation accompanying crystallization at both ends promotes crystallization in the central ribbon, and therefore the block ribbon 51 including such a central ribbon is a member having low iron loss overall.
[0024] As shown in FIG. 2(b), the planar shape of the block ribbon 51 (shape viewed from the Z1-Z2 direction) is similar to that of the magnetic core 100, with a through hole 21 at the center of the circular main body 11, twelve teeth 31 extending radially from the outer surface of the main body 11, and a tip portion 41 having a protrusion protruding in the circumferential direction located at the outer end of each tooth 31.
[0025] Block ribbon 51 has fastening portions 51B in which nanocrystalline ribbons adjacent to each other in the stacking direction (Z1-Z2 direction) are fastened to each other. In block ribbon 51 shown in Fig. 2(a), fastening portions 51B are provided in parts of tip portions 41 of four teeth 31. In this embodiment, fastening portions 51B are formed by laser welding.
[0026] 1(b) is produced by arranging a plurality of block ribbons 51 prepared as an integrated body of a plurality of nanocrystalline ribbons 511. By using block ribbon 51, defects such as breakage of the nanocrystalline ribbons are less likely to occur compared to a case in which nanocrystalline ribbons are laminated one by one to form a laminated core, and as a result, it is possible to improve the quality of magnetic core 100, which is an impregnated coated body of core assembly 50.
[0027] In addition, by changing the number of arrangements of the block ribbons 51, which are easy to handle, specifically by changing the number of laminations, the size of the entire core assembly 50 can be easily adjusted. Therefore, it is possible to easily manufacture a magnetic core 100 having different magnetic properties. Furthermore, since the magnetic properties of the magnetic core 100 can be changed simply by changing the number of laminations of the core assembly 50, the magnetic properties of the magnetic core 100 can be changed without changing the heat treatment conditions of the laminated body of the amorphous ribbon. As described above, when the number of laminated bodies of the amorphous ribbon is changed, it is necessary to set new heat treatment conditions. Therefore, compared to a magnetic core manufactured by such a method, the magnetic core 100 according to this embodiment has excellent quality stability and excellent productivity.
[0028] As described above, when the fixing portion 51B of the block ribbon 51 is a laser welded portion, the adjacent nanocrystalline ribbons 511, 511 are electrically connected through the fixing portion 51B. Therefore, when an eddy current flows through the magnetic core 100, the short-circuit path of the eddy current is the block ribbon 51 unit. That is, since the core assembly 50 of the magnetic core 100 has a structure in which a plurality of block ribbons 51 are arranged, the short-circuit path is the block ribbon 51 unit. Therefore, it is possible to relatively reduce the eddy current loss occurring in the magnetic core 100. On the other hand, when the welding portion is provided so as to fix the entirety of the plurality of magnetic plates constituting the laminated core, as in the laminated core described in Patent Document 2, for example, the short-circuit path of the laminated core is the entirety, and the eddy current loss becomes large.
[0029] The fixing method of the fixing portion 51B is not limited. Adjacent nanocrystalline ribbons in the block ribbon 51 may be fixed by an adhesive. When the fixing portion 51B is located so as to include the side surface of the nanocrystalline ribbon 511, the fixing portion 51B may be a cut portion of the nanocrystalline ribbon 511. As a specific example of such a case, the fixing portion 51B may be a melting portion. FIG. 3(a) is an example of the fixing portion 51B provided on the block ribbon 51, and shows a case where the cutting (cut trace 51C) and welding (fixing portion 51B) of the laminate of the nanocrystalline ribbons 511 are performed simultaneously (melting). FIG. 3(b) is another example of the fixing portion 51B provided on the block ribbon 51, and shows a case where the fixing portion 51B is formed by welding a part of the cut surface of the laminate of the nanocrystalline ribbons 511.
[0030] In the core assembly 50 shown in FIG. 1(b), five block strips 51, 52, 53, 54, 55 arranged along the first direction (Z1-Z2 direction) form a shift-arrangement block strip group in which the respective fixing parts 51B, 52B, 53B, 54B, 55B have parts that are not arranged in the first direction (Z1-Z2 direction). As shown in FIG. 2(b), the block strip 51 has four fixing parts 51B, all of which are located in the protruding part 42 of the tip part 41 of the tooth 31, and the fixing parts 51B are arranged every two teeth 31 of the 12 teeth 31 of the block strip 51. In the core assembly 50, two adjacent block strips (for example, the block strips 51 and 52) have two fixing parts 51B and 52B that are not arranged in the first direction (Z1-Z2 direction). By arranging multiple block ribbons 51, 52, 53, 54, and 55 in the core assembly 50 in this manner, it is expected that spatial variation in the magnetic properties of the core assembly 50 will be less likely to occur, even if the fixed portions 51B, 52B, 53B, 54B, and 55B have magnetic properties different from those of other portions.
[0031] As described above, the core assembly 50 shown in FIG. 1(b) is arranged so that the fixing portion 51B of the block ribbon 51 constituting the core assembly 50 is not aligned with the fixing portion 52B of the adjacent block ribbon 52 in the first direction (Z1-Z2 direction), but is not limited thereto. FIG. 4 is a diagram showing one modified example of a core assembly provided in a magnetic core according to an embodiment of the present invention. As in the core assembly 501 shown in FIG. 4(a), the fixing portions of adjacent block ribbons may be aligned in the first direction (Z1-Z2 direction). In this case, too, there is magnetic continuity but no electrical continuity between two adjacent block ribbons, so that the short-circuit path of the core assembly 501 is each unit of the block ribbons 51, 52, 53, 54, and 55.
[0032] In the core assembly 502 shown in FIG. 4(b), no fixing portion is provided on the outermost surface of the core assembly 502, and a fixing portion is provided on a side surface located inside the outermost surface. Specifically, in the core assembly 502, the fixing portions 51B, 53B, 54B, and 55B are provided on one side surface of the circumferential protrusion 42 at the tip 41 of the tooth 31. In the magnetic circuit of the magnetic component using the magnetic core 100 including the core assembly 502, a magnetic path may be set so as to pass through the outermost side surface of the core assembly 502. In such a case, if a fixing portion is provided on the outermost surface, the magnetic path passing through the fixing portion may affect the characteristics of the magnetic component (for example, the rotation characteristics of a motor). In the core assembly 502, since no fixing portion is provided on the outer side surface of the protrusion 42 corresponding to the outermost surface, it is expected that the magnetic characteristics of the magnetic core 100 including the core assembly 502 will be less affected by the fixing portion.
[0033] In the core assembly 503 shown in FIG. 4(c), a fixing portion 51B is provided on the outer surface of the main body 11 located in a space (corresponding to a part of the slot SL of the magnetic core 100) between two adjacent teeth 31 in the block ribbon 51. When the fixing portion 51B is provided at this position, the effect of forming the fixing portion 51B on the block ribbon 51 can be reduced compared to when the fixing portion 51B is provided on a part of the tooth 31. For example, when the fixing portion 51B is formed on a part of the tooth 31 by laser welding, the tooth 31 may be partially deformed (melted and then solidified) due to heat applied by the laser welding. However, in the case of the core assembly 503, even if deformation occurs when the fixing portion 51B is formed by laser welding, since the fixing portion 51B is provided on the main body 11, the effect of the fixing portion 51B on the magnetic properties of the magnetic core 100 can be reduced compared to when the fixing portion 51B is formed on a part of the tooth 31.
[0034] In this embodiment, the nanocrystalline ribbon 511 is a heat-treated amorphous ribbon made of an Fe-based amorphous alloy material. Specifically, it is a ribbon made of a nanocrystal-containing alloy material having a bcc-Fe phase as a main phase, which is obtained by nanocrystallizing an amorphous ribbon through heat treatment. As will be described later, the multiple nanocrystalline ribbons 511 constituting the block ribbon 51 are obtained by simultaneously heat-treating a stack of amorphous ribbons corresponding to the block ribbon 51.
[0035] The thickness of the block ribbon 51 is set to a thickness that allows the nanocrystalline ribbon 511 to be generated from the amorphous ribbon by this heat treatment. If the laminate of the amorphous ribbons becomes thick, the heat generated when the amorphous ribbons are crystallized is less likely to be released to the outside of the laminate, and the controllability of the heat treatment decreases. Therefore, from the viewpoint of appropriately progressing the heat treatment, it is preferable that an upper limit is set for the thickness of the block ribbon 51. On the other hand, since the nanocrystalline ribbon 511 generated by the heat treatment is hard and brittle, it is preferable that the laminate generated by the heat treatment has a certain number of nanocrystalline ribbons 511 stacked therein in order to improve the handleability. From this viewpoint, it is preferable that a lower limit is set for the thickness of the block ribbon 51.
[0036] As a non-limiting example, the thickness of the block ribbon 51 is preferably 3 mm or less, and may be preferably 2 mm or less. Also, the thickness of the block ribbon 51 may be preferably 200 μm or more, and may be more preferably 500 μm or more.
[0037] Although the manufacturing method of the magnetic core 100 according to this embodiment is not limited, the magnetic core 100 can be manufactured with high productivity by the method described below. Fig. 5 is a flowchart showing an example of a manufacturing method of the magnetic core according to one embodiment (first embodiment) of the present invention.
[0038] As shown in the flow chart of FIG. 5, first, an amorphous ribbon is manufactured by a single roll method or the like (step S101). The obtained amorphous ribbon is cut to an appropriate length, and the obtained ribbon piece is punched to obtain a punched member having a shape in a plan view (shape seen from the Z1-Z2 direction) shown in FIG. 2 (step S102). A plurality of the obtained punched members are stacked to obtain a laminate (step S103). As described above, the amorphous ribbon is tougher than the nanocrystalline ribbon after heat treatment, so that the ribbon is less likely to chip even when stacked.
[0039] A blocking step is performed in which the outer surface of the obtained laminate is laser-welded at a plurality of locations to obtain a block body (step S104). The obtained block body is heat-treated to obtain a block ribbon 51 (step S105). As described above, the conditions of the heat treatment are set so that crystallization proceeds appropriately in all of the amorphous ribbons constituting the block body, and defects caused by heat generated by crystallization (production of unnecessary substances such as compounds, burnout, etc.) are appropriately suppressed.
[0040] A plurality of block ribbons 51 obtained by the heat treatment are stacked to obtain the core assembly 50 shown in Fig. 1(b). At this time, rotation stacking is performed in which adjacent block ribbons 52 are rotated around the central axis of the through-hole 21 relative to the block ribbon 51 so that adjacent fastening parts (e.g., fastening parts 51B and 52B) are not aligned in the first direction (Z1-Z2 direction) (step S106).
[0041] If necessary, the core assembly 50 is subjected to a secondary heat treatment (step S107), and then impregnation coating is performed (step S108) to obtain the magnetic core 100. After the impregnation coating is performed, shape adjustment such as deburring may be performed if necessary (step S109).
[0042] Next, a method for efficiently manufacturing a plurality of block ribbons 51 included in the core assembly 502 shown in FIG. 4(b) including simultaneously heat-treating a plurality of core ribbon parts 300 will be described with reference to FIG. 6, FIG. 8, and FIG. 9. FIG. 6 is a flow chart showing another example of a method for manufacturing a magnetic core according to an embodiment of the present invention. FIG. 8(a) is an explanatory diagram of a manufacturing process of a hoop material made of an amorphous ribbon for forming a nanocrystalline ribbon included in a magnetic core according to an embodiment of the present invention. FIG. 8(b) is an explanatory diagram of a configuration of a hoop material made of an amorphous ribbon manufactured by the manufacturing process of FIG. 8(a). FIG. 8(c) is an explanatory diagram of a punched portion of a hoop material made of an amorphous ribbon shown in FIG. 8(b). FIG. 9(a) is a diagram showing a coupled laminate obtained by dividing a hoop material made of an amorphous ribbon shown in FIG. 8(b). FIG. 9(b) is a diagram explaining a heat treatment of the coupled laminate of FIG. 9(a). FIG. 9(c) is a diagram showing an arrangement of a heat treatment device in the heat treatment of FIG. 9(b).
[0043] In the manufacturing method shown in the flowchart of Fig. 6, as in the manufacturing method shown in the flowchart of Fig. 5, first, an amorphous ribbon is manufactured by a single roll method or the like (step S201). Since the obtained amorphous ribbon has higher toughness than a nanocrystalline ribbon, the obtained amorphous ribbon is wound up into a roll (amorphous roll 201).
[0044] Next, a hoop material 205 is generated by punching (step S202). Fig. 8(a) shows a manufacturing method of the hoop material 205 by the roll-to-roll method. An amorphous ribbon 202 is fed from an amorphous roll 201 in one direction (specifically, the X1 side of the X1-X2 direction), and the amorphous ribbon 202 is punched by a punching die (upper die 203, lower die 204).
[0045] 8(b), the obtained hoop material 205 is arranged in the extending direction (X1-X2 direction) of the substrate portion 211, and includes a core ribbon portion 300 which will ultimately be a direct component of the magnetic core 100, a substrate portion 211 extending in the in-plane direction (specifically, the X1-X2 direction) of the core ribbon portion 300, and a punched portion 350 including a connecting bar 212 connecting the core ribbon portion 300 and the substrate portion 211. The substrate portion 211 is provided with a hole (positioning portion 213) for positioning.
[0046] As shown in FIG. 8(c), the shape of the core ribbon portion 300 of the punched portion 350 in a plan view (shape seen from the Z1-Z2 direction) is similar to that of the block ribbon 51, and has a through portion 320 at the center of a circular main body portion 310, 12 teeth 330 extending radially from the outer surface, and a tip portion 340 having a protruding portion 341 protruding in the circumferential direction is located at the outer end of each tooth 330. As shown in FIG. 8(c), some of the connecting bars 212 are provided so as to connect to the protruding portions 341 protruding in the circumferential direction (Y1-Y2 direction) at the tip portions 340 of the two teeth 330 extending along the X1-X2 direction. Other connecting bars 212 are provided so as to connect to the protruding portions 341 protruding in the circumferential direction (X1-X2 direction) at the tip portions 340 of the two teeth 330 extending along the Y1-Y2 direction. Therefore, the cut portion CP of the connecting bar 212 is not positioned so as to be connected to the outermost surface of the tip portion 340. Therefore, the block ribbon 51 obtained from the punching processing portion 350 shown in Fig. 8(c) does not have the fixing portion 51B (i.e., the cut mark 51C) positioned on the outermost surface as shown in Fig. 4(b).
[0047] The cut mark 51C may have a different crystal state from other parts, regardless of whether the cutting method is laser cutting or mechanical cutting. Therefore, the magnetic properties of the magnetic core 100 may differ from other parts at the part where the cut mark 51C is located. Therefore, when the magnetic path of the magnetic circuit of the magnetic component including the magnetic core 100 passes through the cut mark 51C, the magnetic properties may change at that part, and as a result, the stability of the magnetic properties of the magnetic component may be affected. It is possible to minimize such effects by optimizing the cutting method. The magnetic circuit of the magnetic component using the magnetic core 100 including the block ribbon 51 may have a magnetic path passing through its outermost side surface. For example, by using the punched part 350 shown in FIG. 10(a), the core assembly 502 shown in FIG. 4(b) can be obtained, so that the possibility that the magnetic path of the magnetic circuit of the magnetic component passes through the cut mark 51C can be further reduced.
[0048] The hoop material 205 obtained by the punching process is wound up to become a roll material 206. Next, the hoop material 205 is unwound from the roll material 206 and cut into small pieces to obtain a linked member 251 having a predetermined number (e.g., 3) of linked punched portions 350 (step S203). As shown in FIG. 9(a), a plurality of the linked members 251 obtained are stacked in the Z1-Z2 direction to obtain a linked laminate 360 (step S204). Here, by using the positioning portion 213 of each linked member 251, a plurality of linked members 251 can be stacked in the Z1-Z2 direction easily and without contacting the core ribbon portion 300.
[0049] Next, the obtained coupled laminate 360 is subjected to a heat treatment (step S205). As shown in Fig. 9(b) and Fig. 9(c), a plurality of sets of heat treatment devices 395, 396 are prepared according to the number of laminates of the core ribbon portion 300 included in the coupled member 251 of the coupled laminate 360, and the laminates of the core ribbon portion 300 are sandwiched between the sets of heat treatment devices 395, 396 from the stacking direction (Z1-Z2 direction) of the coupled laminate 360. The heat treatment devices 395, 396 are for controlling the temperature of the core ribbon portion 300, and each of them includes a heat sink 370, 371 having a substantially cylindrical shape and directly contacting the core ribbon portion 300, and a heater block 390, 391 for heating the heat sink 370, 371. Thus, the heat treatment devices 395, 396 have a function of applying heat to the core ribbon portion 300 and a function of receiving heat from the core ribbon portion 300. By arranging a plurality of pairs of heat treatment devices 395, 396 in this manner, it is possible to equalize the conditions of heat treatment applied to each of the laminates of the plurality of core ribbon portions 300 of the coupled laminate 360. The conditions of the heat treatment are set so that crystallization proceeds appropriately in all of the amorphous ribbons constituting the core ribbon portion 300 of the coupled laminate 360 and defects caused by heat generated by crystallization (such as generation of unnecessary substances such as compounds and burnout) are appropriately suppressed.
[0050] By carrying out the heat treatment in this manner, the amorphous ribbon constituting the core ribbon portion 300 of the coupled laminate 360 is crystallized to become the nanocrystalline ribbon 511. Next, the connection portion (cut portion CP) of the protruding portion 341 with the connecting bar 212 is laser-melted to separate the laminate of the core ribbon portion 300 (nanocrystalline ribbon 511), and the multiple nanocrystalline ribbons 511 constituting this laminate are fixed to obtain the block ribbon 51 shown in Fig. 4(b) (step S206). Therefore, the fixed portion 51B of the block ribbon 51 manufactured by the manufacturing method shown in the flowchart of Fig. 6 also becomes the cut mark 51C.
[0051] Thereafter, similarly to the steps shown in Fig. 5, rotational lamination (step S207) and, if necessary, secondary heat treatment (step S208) are performed to obtain the core assembly 50 shown in Fig. 1(b). Further, impregnation coating (step S209) and, if necessary, shape adjustment (step S210) are performed to obtain the magnetic core 100 shown in Fig. 1(a).
[0052] FIG. 10(a) is a diagram for explaining a modified example of the heat treatment of the coupled laminate of FIG. 9(b), and FIG. 10(b) is a plan view showing the shape of a heating member used in the heat treatment of FIG. 10(a).
[0053] As shown in FIG. 9(b), when the heat sinks 370, 371 provided in the heat treatment devices 395, 396 have a substantially cylindrical shape, the cut portion CP (see FIG. 8(c)) directly contacts the heat sink 370 as shown in FIG. 9(c). Therefore, in the coupled laminate 360 after the heat treatment step (step S205), the cut portion CP is also crystallized by the heat treatment. Therefore, the cut portion CP may have a reduced cutting workability. As described above, although the protrusion 341 to which the cut portion CP is connected is unlikely to have a magnetic path passing therethrough, if the cut workability is reduced, the shape uniformity of the cut mark 51C may be reduced, which may affect the maintenance of the shape quality of the block ribbon 51.
[0054] 10, if the shape of the heat sinks 370A, 371A in a plan view (shape seen from the Z1-Z2 direction) corresponds to the shape of the core ribbon portion 300 in a plan view, in the heat treatment process (step S205), the portion of the connecting bar 212 connected to the protruding portion 341 of the tip portion 340 is not heat treated and remains an amorphous alloy. Therefore, in the coupled laminate 360 after the heat treatment, the cutting processability of the cutting portion CP is good, and even if the fixing portion 51B is located on the side surface of the protruding portion 341 of the tip portion 340 of the block ribbon 51 as shown in FIG. 4(b), the shape quality is not likely to deteriorate.
[0055] In the manufacturing method shown in Fig. 6, the cutting process and the blocking process are performed simultaneously by laser melting, but these steps may be performed separately. Fig. 7 is a flowchart showing another example of the manufacturing method of the magnetic core according to the embodiment of the present invention.
[0056] The flowchart shown in FIG. 7 is different from the flowchart shown in FIG. 6 in that the "separation / cutting / blocking" step S206 is divided into a separation / cutting step (step S206A) and a blocking step (step S206B). In this case, the separation / cutting step is performed by, for example, mechanical cutting, and the blocking step is performed by, for example, laser welding. Also, the flowchart shown in FIG. 7 is different from the flowchart shown in FIG. 6 in that the heat treatment step (step S205) is performed after the blocking step (step S206B). When the part made of an amorphous alloy is subjected to the heat treatment step (step S205), it becomes nano-crystallized and the cutting workability is reduced. Therefore, if the separation / cutting step (step S206A) is performed before the heat treatment step (step S205), it is easy to ensure good cutting workability of the connecting bar 212. Furthermore, when the amorphous ribbon is crystallized by heat treatment to become the nanocrystalline ribbon 511, it becomes brittle and difficult to handle. However, if a blocking step (step S206B) is performed before the heat treatment step (step S205), the product obtained by the heat treatment becomes the block ribbon 51 in which multiple nanocrystalline ribbons 511 are stacked and fixed together, so that good handleability can be ensured.
[0057] Fig. 11(a) is a plan view showing an example of a block ribbon manufactured by the manufacturing method shown in the flowchart of Fig. 7. Fig. 11(b) is a diagram for explaining a fixing portion of the block ribbon of Fig. 11(a). The block ribbon 510 shown in Fig. 11 has a cutting remainder 214 at the outer end of the tip portion 41 of the tooth 31. The cutting remainder 214 is a cutting remainder when the cutting portion CP of the connecting bar 212 is cut in the separation cutting step (step S206A). In the block ribbon 510 shown in Fig. 11, similarly to the core assembly 503 shown in Fig. 4(c), the fixing portion 51B is provided by laser welding on the outer surface of the main body portion 11 that forms a space corresponding to the slot SL.
[0058] Fig. 12(a) is a plan view showing the shape of an amorphous ribbon for forming a core assembly included in a magnetic core according to another embodiment (second embodiment) of the present invention. Fig. 12(b) is a diagram showing the shape of a block ribbon formed from the amorphous ribbon of Fig. 12(a). Fig. 13(a) is a diagram showing a core assembly including the block ribbon of Fig. 12(b). Fig. 13(b) is a diagram showing a core assembly obtained by further combining the core assemblies of Fig. 13(a).
[0059] In the core assembly 90 according to the second embodiment of the present invention, the block ribbons 70 are arranged side by side in directions other than the stacking direction (Z1-Z2 direction) of the nanocrystalline ribbons 60 that constitute the block ribbon 70.
[0060] 12(a), nanocrystalline ribbon 60 according to the second embodiment includes main body 61 having a shape obtained by dividing a ring into quarters, protruding portions 62 protruding in the circumferential direction of the ring from main body 61, recessed portions 63 recessed in the circumferential direction of the ring from main body 61, and teeth 64 protruding from the inner circumferential side of the ring toward the center side of the ring. Protruding portions 62 and recessed portions 63 are shaped to be engageable with each other so as to be connectable with other nanocrystalline ribbons 60.
[0061] A laminate formed by stacking a plurality of nanocrystalline ribbons 601 along the thickness direction (Z1-Z2 direction) is fixed to obtain a block ribbon 70 having a fixed portion 70B. The block ribbon 70 has a fitting convex portion 71 based on the convex portion 62 of the nanocrystalline ribbon 60 and a fitting concave portion 72 based on the concave portion 63 of the nanocrystalline ribbon 60 so that the block ribbon 70 can fit with another block ribbon 70.
[0062] As shown in FIG. 13(a), the core assembly 90 according to this embodiment has a ring assembly 80 in which four block ribbons 70 are fitted together at fitting portions 80C, and the ring assembly 80 has an overall shape of a ring. The arrangement direction of the block ribbons 70 in the ring assembly 80 is different from the stacking direction (Z1-Z2 direction) of the nanocrystalline ribbons 60. As shown in FIG. 13(b), a plurality of ring assemblies 80 (three in FIG. 13(b)) are stacked to form the core assembly 90. The fixing portions 81B, 82B, and 83B of the core assembly 90 originating from the fixing portion 70B of the block ribbon 70 are arranged in the stacking direction (Z1-Z2 direction), but the core assembly 90 is electrically separated for each block ribbon 70, so that the short-circuit path is limited to the block ribbon 70. For this reason, the magnetic core including the core assembly 90 is less likely to have large eddy current loss.
[0063] Fig. 14(a) is an external view of a motor, which is an example of a magnetic product using a magnetic component having a magnetic core according to an embodiment of the present invention. Fig. 14(b) is an external view of a rotor, which is one of the magnetic components included in the motor of Fig. 14(a). Fig. 14(c) is an external view of a stator, which is another of the magnetic components included in the motor of Fig. 14(a). As shown in Fig. 14(a), in a motor 700, a rotating shaft 702 passing through the center of the bottom surface of a cylindrical motor body 701 protrudes from the motor body 701 toward the Z1 side in the Z1-Z2 direction.
[0064] 14(b) is disposed inside the motor body 701 so as to be rotatable about a rotation axis in the Z1-Z2 direction. The rotor 710 includes a rotor body 711 having a hollow cylindrical shape with one side of the bottom surface (the Z1 side in the Z1-Z2 direction) open, and a rotation axis 702 fixed to the center of the other side of the bottom surface (the Z2 side in the Z1-Z2 direction) of the rotor body 711. A plurality of magnets 712 are disposed on the inner wall of the rotor body 711 in a line in the circumferential direction.
[0065] A stator 720 having a cylindrical outer shape is disposed between a rotor body 711 and a rotating shaft 702 of the rotor 710. The stator 720 is composed of a magnetic core 100 according to one embodiment of the present invention and a coil 721 wound around each of the teeth 30. The rotating shaft 702 is inserted through the through hole 20 of the magnetic core 100. The magnets 712 of the rotor 710 are provided on the inner wall of the rotor body 711 so as to face each of the tip portions 40 of the teeth 30 of the magnetic core 100.
[0066] The magnetic core 100 according to one embodiment of the present invention has excellent magnetic properties because the core assembly 50, in which a plurality of block ribbons 51, which are laminates in which a plurality of nanocrystalline ribbons 511 are fixed by fixing parts 51B, are fixed by an impregnation coat. Specifically, the plurality of block ribbons 51 in the core assembly 50 are magnetically connected but not electrically connected, so that eddy current loss is small. Also, when the magnetic core 100 includes the core assembly 502 (see FIG. 4(b)), the fixing parts 51B are not provided on the outermost surface of the tip part 41, so that the magnetic circuit of the motor 700 is likely to be stable. Therefore, the motor 700 is expected to have particularly stable rotation characteristics.
[0067] The above-described embodiments are described to facilitate understanding of the present invention, and are not described to limit the present invention. Therefore, each element disclosed in the above-described embodiments is intended to include all design modifications and equivalents that fall within the technical scope of the present invention. In the above-described embodiments, the block ribbon 51 includes the fixing portion 50B, but is not limited to this. The block ribbon 51 has a structure in which a plurality of nanocrystalline ribbons 511 having a bcc-Fe phase as a main phase are stacked, and it is sufficient that the iron loss of the central ribbon is lower than the iron loss of the surface layer ribbons of the stacked nanocrystalline ribbons 511. EXAMPLES
[0068] The effects of the present invention will be described below based on examples, but the present invention is not limited to these.
[0069] Example 1 According to the manufacturing method shown in the flowchart of FIG. 5, a block body 380 (a laminate in which a plurality of core ribbon portions 300 made of amorphous ribbons are laminated and a fixing portion 380B is provided on a side surface of the laminate by laser welding; see FIG. 15 ) obtained by carrying out the blocking step (step S104) was subjected to a heat treatment step (S105) as follows.
[0070] Fig. 15 is an explanatory diagram of a heat treatment device used in the heat treatment step of the embodiment. As shown in Fig. 15, the heat treatment device 397 includes heat treatment devices 395 and 396 arranged on both sides of the stacking direction (Z1-Z2 direction) of the block body 380. The heat treatment devices 395 and 396 are for controlling the temperature of the block body 380, and include heat sinks 370 and 371 having a substantially cylindrical shape and directly contacting the core ribbon portion 300, and heater blocks 390 and 391 for heating the heat sinks 370 and 371, respectively.
[0071] From the viewpoint of improving the heating uniformity of the block body 380, it is preferable that the shape of the heat sinks 370, 371 as viewed from the stacking direction (Z1-Z2 direction) of the block body 380 is slightly larger than the shape of the block body 380, and that all of the surfaces on both sides of the block body 380 in the stacking direction are in contact with the heat sinks 370, 371. Furthermore, from the viewpoint of more stably improving the heating uniformity of the block body 380, it is preferable that the heat sinks 370, 371 are also located in an outer region beyond the outer edge of the block body 380. As a non-limiting example, when the shape of the block body 380 as viewed from the stacking direction (Z1-Z2 direction) is circular, the diameter φ2 of the inscribed circle of the shape of the heat sinks 370, 371 as viewed from the stacking direction (Z1-Z2 direction) of the block body 380 is preferably 102% or more of the diameter φ1 of the circle of the block body 380, and more preferably 105% or more.
[0072] In the heat treatment processing device 397, a jig 375 is provided around the heat sinks 370, 371 in the XY plane direction, with a space between the stacked body consisting of the heat sinks 370, 371 and the block body 380. A heat insulating material 376 is provided between the jig 375 and the heater blocks 390, 391, and the jig 375 is thermally isolated from the heater blocks 390, 391. The jig 375 is for discharging heat released in the XY plane direction from the stacked body consisting of the heat sinks 370, 371 and the block body 380 to the outside of the heat treatment processing device 397 (heat dissipation function). From the viewpoint of appropriately performing the heat dissipation function of the jig 375, the maximum distance d between the jig 375 and the block body 380 in the XY plane direction is preferably 1 cm or less, more preferably 5 mm or less, and particularly preferably 2 mm or less.
[0073] In the first embodiment, the block body 380 includes 30 amorphous ribbons, each of which is 30 μm thick, and has a thin cylindrical shape with a diameter of 35 mm and a thickness of 0.9 mm. The heat sinks 370 and 371 have a cylindrical shape with a thickness of 10 mm and a bottom surface formed of a circle with a diameter of 37 mm. The jig 375 is made of a plate-like body that has a through hole with an inner diameter of 40 mm and whose through axis is in the Z1-Z2 direction and can be separated in the Z1-Z2 direction, and a laminated body consisting of the heat sinks 370 and 371 and the block body 380 is arranged inside the through hole. Therefore, the maximum value d of the separation distance between the jig 375 and the block body 380 in the XY plane direction was 2.5 mm.
[0074] Heat treatment was performed on block body 380 with the maximum heat treatment temperature of heat sinks 370 and 371 set to 450° C., and block ribbon 51 was obtained from block body 380. The obtained block ribbon 51 was separated into a plurality of nanocrystalline ribbons 511, and the diffraction spectrum of nanocrystalline ribbons 511 at predetermined stacking positions (1st, 7th, 15th, 22nd, and 30th sheets counting from Z1 side in the Z1-Z2 direction) was measured by an X-ray diffraction device (XRD), and the crystal grain size (unit: nm) of the nanocrystals was measured from the obtained diffraction spectrum. In addition, for nanocrystalline ribbon 511 whose diffraction spectrum was measured, a fluctuating magnetic flux (W15 / 50) alternating at 50 Hz with a maximum magnetic flux density of 1.5 T was applied using a BH analyzer to measure the iron loss (unit: W / kg). The results are shown in Table 1 and FIG. 16.
[0075] [Table 1]
[0076] As shown in FIG. 16, the 15th nanocrystalline ribbon 511 (central ribbon located at the center of the thickness direction (Z1-Z2 direction) of the block ribbon 51) has lower iron loss than the first nanocrystalline ribbon 511 and the 30th nanocrystalline ribbon 511 (surface layer ribbon located at the surface layer of the block ribbon 51). In addition, the central ribbon has a smaller crystal grain size than the surface layer ribbon. This result means that the heat treatment of all the amorphous ribbons constituting the block body 380 has progressed appropriately. If the heat treatment does not progress appropriately, heat generated when the amorphous ribbon located near the center among the amorphous ribbons constituting the block body 380 is nanocrystallized is not properly released from the block body 380, and the crystal grain size of the nanocrystalline ribbon (central ribbon) obtained from the amorphous ribbon located near the center is likely to be larger than that of the nanocrystalline ribbon (surface layer ribbon) located at the surface layer, and the iron loss of the central ribbon is likely to be larger than that of the surface layer ribbon.
[0077] (Examples 2 to 5) The number of stacked amorphous ribbons in the block body 380 was set to 10 (Example 2), 20 (Example 3), 50 (Example 4), and 100 (Example 5), and the same heat treatment as in Example 1 was performed. The results are shown in Tables 2 to 5 and Figs. 17 to 20. Each table shows the maximum heat treatment temperature of the heat sinks 370 and 371. Note that in Example 5, there was a nanocrystalline ribbon 511 for which the iron loss was measured but the crystal grain size was not measured.
[0078] [Table 2]
[0079] [Table 3]
[0080] [Table 4]
[0081] [Table 5]
[0082] In all cases where the number of laminated sheets was between 10 and 100, the central ribbon had lower iron loss and larger crystal grain size than the surface layer ribbons, as in the case where the number of laminated sheets was 30.
[0083] Comparative Example 1 In the heat treatment processing device 397 used in Example 1, a comparative jig consisting of a plate-like body separable in the Z1-Z2 direction and having a through hole with an inner diameter of 120 mm whose through axis is in the Z1-Z2 direction was used, and a laminate consisting of heat sinks 370, 371 and block body 380 was placed inside the through hole of the comparative jig. Therefore, the maximum distance d between the comparative jig and block body 380 in the XY plane direction was 42.5 mm.
[0084] The heat treatment was performed on the block body 380 with the maximum heat treatment temperature of the heat sinks 370, 371 set to 430°C, and the block ribbon 51 was obtained from the block body 380. The maximum heat treatment temperature was set lower than in Example 1 because it was assumed that the heat generated in the block body 380 would be relatively less likely to be released to the outside since the maximum value d of the separation distance in the XY plane direction between the comparative jig and the block body 380 was wider than in Example 1. The measurement results of the iron loss and crystal grain size of the nanocrystalline ribbon 511 of the obtained block ribbon are shown in Table 6 and FIG.
[0085] [Table 6]
[0086] 21, the 15th nanocrystalline ribbon 511 (central ribbon) had a higher iron loss than the first nanocrystalline ribbon 511 and the 30th nanocrystalline ribbon 511 (surface layer ribbon) located in the surface layer of the block ribbon 51. Moreover, there was no tendency for the central ribbon to always have a smaller crystal grain size than the surface layer ribbon, as in Example 1.
[0087] Based on the above results, the relationship between the average core loss and grain size and the number of layers and the layer thickness was confirmed. The results are shown in Table 7 and Figures 22 and 23.
[0088] [Table 7]
[0089] As shown in Table 7 and Figs. 22 and 23, there was a tendency for the core loss and crystal grain size to increase as the number of laminations or the lamination thickness increased.
[0090] In addition, the relationship between the heat treatment temperature (heat sink surface temperature) and the number of layers and the layer thickness was confirmed. The results are shown in Table 8 and Figures 24 and 25.
[0091] [Table 8]
[0092] As shown in Table 8 and Figures 24 and 25, there was a tendency for the heat treatment temperature (maximum heat treatment temperature) set to prevent thermal runaway to decrease as the number of layers or the layer thickness increased. [Explanation of symbols]
[0093] 10, 11, 61, 310: Main body 20:Through hole 21, 320: Penetration 30, 31, 64, 330: Teeth 40, 41, 340: Tip 42, 341:Protrusion 50, 90, 501, 502, 503: Core Assembly 51, 52, 53, 54, 55, 510, 70: Block thin strips 51B, 52B, 53B, 54B, 55B, 70B, 380B, 81B, 82B, 83B: Fixing part 51C: Cutting marks 60: Nanocrystalline ribbon 62: Convex 63: Recess 71: Fitting protrusion 72: Fitting recess 80, 81, 82, 83: Ring assemblies 80C: Fitting part 100: Magnetic core 201: Amorphous roll 202: Amorphous ribbon 203: Upper mold 204: Lower mold 205: Hoop material 206: Roll material 211: Base material part 212: Connecting bar 213: Positioning section 214: Cutting remainder 251: Composite members 300: Core thin strip 350: Punching section 360: Interlinked laminate 370, 371, 370A, 371A: Heat sink 375: Jig 376: Insulation material 380: Block letter 390, 391: Heater block 395, 396: Heat treatment equipment 397: Heat treatment equipment 511, 601: Nanocrystalline ribbon 700: Motor 701: Motor body 702: Rotation axis 710: Rotor 711: Rotor body 712: Magnet 720: Stator 721: Coil CP: Cutting section SL: Slot
Claims
1. A method for manufacturing a core assembly having a block ribbon having a structure in which a plurality of nanocrystalline ribbons having a bcc-Fe phase as a main phase are stacked, comprising the steps of: The manufacturing method includes: providing a fixing portion by laser welding on a side surface of a first laminate formed by laminating a plurality of core ribbon portions each made of an amorphous ribbon to obtain a block body; a heat treatment including: sandwiching the block body between two heat sinks in a stacking direction of the block body; arranging a jig around the two heat sinks in a direction perpendicular to the stacking direction of the two heat sinks with a space from a second stack including the two heat sinks and the block body; and heating the two heat sinks with a heater block, thereby converting the amorphous ribbon into the nanocrystalline ribbon and obtaining a block ribbon having a thickness of 3 mm or less from the block body; and impregnating and coating a third laminate formed by laminating a plurality of the block ribbons to obtain the co-assembly. Equipped with the jig is thermally isolated from the heater block and discharges heat emitted from the laminated body including the heat sink and the block body to the outside; The maximum distance between the jig and the block body in the direction perpendicular to the stacking direction is 1 cm or less. A method for manufacturing a core assembly comprising the steps of:
2. The shape of the block body as viewed from the stacking direction is a circle having a diameter of φ1, The method for manufacturing a core assembly according to claim 1 , wherein a diameter φ2 of an inscribed circle of the shape of the heat sink as viewed from the stacking direction is 102% or more of the diameter φ1.
Citation Information
Patent Citations
JP1968029604Y1
JP1982093055U
Stator of rotary electric machine
JP2007159300A
Magnetic iron core and converter circuit
JP2015076579A
Stator laminated iron core and manufacturing method of the same
JP2017108578A